Die Bedeutung der Lehrwerkanalyse für den modernen Fremdsprachenunterricht - Ciepielewska, Luiza (Glottodidactica, 2000)
The demand for language courses and at the same time for language course books increases over the years continuously so a wide range of possibilities is available to teachers nowadays. The analysis can prove to be helpful in case of doubt as to which course book to choose for a particular student's group. The aim of this article is to present the rising importance of the analysis for modem language courses. Throughout the article the author gives an outline of analysis history, presents factors which made the analysis nowadays necessary and discusses analysis components. At the end of the article titles of periodicals are listed in which ready analysis of different course books can be found.